Research note: a socioeconomic index for the INCAP Longitudinal Study 1969-77 - Maluccio, John; Murphy, Alexis; Yount, Katherine M. (SAGE Publications, 2005)
In this note, we calculate and describe proxy measures that account for variation in standard of living across subjects in the Institute of Nutrition of Central America and Panama (INCAP) Longitudinal Study (1969–77), at the time of the original intervention. Using principal components analysis, we construct two linear indices from an array of household consumer durable goods and housing characteristics, measured at the nuclear family level in the 1975 cross-sectional census. The two indices perform well on three dimensions. First, they are internally coherent in that average ownership and quality of housing characteristics increase with the principal component score. Second, they are robust in that the different approaches yield similar results, for example, in classifying nuclear families into tertiles. And third, they are consistent in that they yield results similar to scores constructed by previous researchers. The indices can be used as background controls in analyses of the INCAP Longitudinal Study (1969–77) data and subsequent follow-up studies, including the Human Capital Study 2002–04. Several articles presented in this supplement to the Food and Nutrition Bulletin used the 1975 index.